The short-term effects of hydrotherapy on pain and self-perceived functional status in individuals living with osteoarthritis of the knee joint - Kganetso Sekome; Stacey Maddocks (South African Journal of Physiotherapy, 2019)
Background: People living with knee osteoarthritis (OA) commonly present with difficulty in walking long distances, ascending and descending stairs or rising from sitting. These functional limitations have been shown to have a negative effect on their overall activities of daily living.